Solid Lipid Nanoparticles: A Trending Slant for Drug Delivery System - Hangargekar, Mr. Sachin R. (Asian Journal of Pharmaceutics (AJP), 2021)
Drug delivery systems have opened various doors to fulfill the requirements of chemotherapy. It improves therapeutic effects of already efficient molecules by delivering it to the targeted site. Research area achieved a high peak in the aspect of lipid-based nano-drug delivery system. Conventional oral therapy has various problems especially lower oral bioavailability of a drug. To overcome such problems, researcher found a way in the form of solid lipid nanoparticles (SLNs). Newest form of medication carrier system, that is, SLN concept firstly introduced in December 1991. It is a system of medication carrier over the traditional colloidal carriers. It mainly includes nanoparticles ranges of spherical stable lipid cells, scattered in fluid surfactant. It includes of nanometer ranges of spherical stable lipid cells, which are often scattered in fluid surfactant arrangement or in water. The main issues raised in previous type of carrier systems are poor water soluble and under development; absolutely having low bioavailability. In this type we have to prepare medicine with physiologically well tolerated lipids is the main advantage of this system to achieve good therapeutic outcomes. Lipid-based nanoparticles are SLNs which has size in between 10 and 1000 nm. This review will focuses on SLNs and their applications in various aspects. Applications comprise targeted therapy in brain tumors. Along with this treatment of metastatic breast cancer can also achieve using SLNs.